The effect of polishing protocol on surface gloss of different restorative resin composites. Issue 1 (1st January 2020) - Lassila, Lippo; Säilynoja, Eija; Prinssi, Roosa; Vallittu, Pekka K.; Garoushi, Sufyan
Abstract: Aim: The purpose of this in vitro study was to determine the effects of different polishing protocols on the surface gloss (SG) of different commercial dental resin composites (RCs). Material and methods: A total of 147 block-shaped specimens (40 mm length × 10 mm width × 2 mm thick) were made from conventional RCs (G-aenial Ant. and Flo X), bulk-fill RC (Filtek Bulk Fill), fluoride-releasing RCs (BEAUTIFIL II, ACTIVA-Restorative) and discontinuous microfiber-reinforced RCs (Alert and everX Flow). Each group was subdivided into seven subgroups ( n = 3), according to polishing protocol: Laboratory-machine polishing with different siliconcarbide paper grits (G1: 320) → (G2: 800) → (G3: 1200) → (G4: 2000) → (G5: 4000). Chairside-hand polishing using a series of Sof-Lex spiral (G6) and abrasive polishing points (G7). Glossmeter was used to determine the SG at 60° incidence angle. SG was measured before and after polishing. Three-dimensional (3 D) noncontact optical profilometer and scanning electron microscopy (SEM) analysis were performed. Data were analyzed using ANOVA ( p = .05). Results: Significant differences in SG (ranged 3–93 GU) were found according to the type of polishing protocol and RC ( p < .05). Specimens polished with 4000 grit paper showed the highest SG (93 GU) values among all the groups tested. Conclusions: The tested chairside-hand polishing protocols presented lower SG values than laboratory-machine polishing (4000 silicon paper grit) and unpolished surfaces.